De Governador Valadares e Criciúma para Boston - Glaucia de Oliveira Assis (Nuevo mundo - Mundos Nuevos, 2007)
The recent emigration of Brazilian people, in the late twentieth century, has placed Brazil in the new flow of worldwide population. Through the analysis of different points of departure, this paper intends to demonstrate that the migratory process does not only result from a rational choice, but also social networks (kinship and friendship) in which men and women are placed, contributing to new arrangements of family and gender relationships. The objective is to analyze the aspect of the social networks of the new emigrants coming from Criciúma and Governador Valadares and heading to Boston in the United States, showing how complex friendships, and economic and family relationships have been built up between these places. Following the trajectory of the emigrants, the work discusses data from fieldwork in Criciúma (SC) and in the Boston area, in the United States. The data, emerged from the interviews and participant observation, has shown that women do not just wait in their homeland for their husbands or children to return, but have an integral participation in the process and helping to form the migration networks. The data also made evident other points of migration besides Governador Valadares (MG), suggesting that social networks of the Brazilian migration have matured.